2008
DOI: 10.1007/s11240-008-9481-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cytokinins on growth and sexual organ development in the gametophyte of Blechnum spicant L.

Abstract: In this study, we report the role of exogenous and endogenous cytokinins on growth and sexual organ development in the fern Blechnum spicant L. Sporederived gametophytes (SG) were cultured in full-strength Murashige and Skoog (1962) liquid medium supplemented with (a) 4.44 lMN 6 -benzyladenine (BAP), (b) a crude extract from mature female gametophytes, and (c) 4.44 lM BAP in combination with the crude extract from mature gametophytes, respectively. Both BAP and the crude extract delayed the gametophyte develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
1
16
0
2
Order By: Relevance
“…To determine the importance of plant growth regulators in sex expression in the gametophyte of B. spicant , the endogenous levels of several gibberellins and cytokinins were determined by mass spectrometry. The obtained data indicated that no differences in the endogenous content of the gibberellins GA 1 , GA 3 , GA 7 , GA 7 , GA 9, and GA 20 were found between sexes ; however, differences in the endogenous content of the cytokinins were documented, increasing the content of iP (isopentenyl adenine) and iPR (isopentenyl adenosine in female gametophytes more than 300 and 400 times respect to the male ones . In the light of these results, it seems that antheridiogenesis in the gametophyte of different species might be governed in different ways.…”
Section: Discussionmentioning
confidence: 85%
“…To determine the importance of plant growth regulators in sex expression in the gametophyte of B. spicant , the endogenous levels of several gibberellins and cytokinins were determined by mass spectrometry. The obtained data indicated that no differences in the endogenous content of the gibberellins GA 1 , GA 3 , GA 7 , GA 7 , GA 9, and GA 20 were found between sexes ; however, differences in the endogenous content of the cytokinins were documented, increasing the content of iP (isopentenyl adenine) and iPR (isopentenyl adenosine in female gametophytes more than 300 and 400 times respect to the male ones . In the light of these results, it seems that antheridiogenesis in the gametophyte of different species might be governed in different ways.…”
Section: Discussionmentioning
confidence: 85%
“…In other higher plants, cytokinin levels increased during flowering induction (Lejeune et al 1994;Corbesier et al 2003). Higher cytokinin concentrations were found in female gametophytes than in male gametophytes in Blechnum spicant (Menéndez et al 2009). …”
Section: Discussionmentioning
confidence: 90%
“…We did not analyze cZ, but the levels of tZ were low or not detected. Menéndez et al (2009) reported differences in the endogenous content of tZ, tZR, DHZ, iP and iPR linked to gender in B. spicant L., being especially high the contents of iP and iPR contents in female gametophytes. More recently, analyses of different tissues of A. nidus (H. Fernández, personal communication) showed higher levels of tRZ and iP than of tZ and DHZ, with the lowest levels corresponding to tZ.…”
Section: Discussionmentioning
confidence: 97%